PENGARUH MODEL PBL (PROBLEM BASED LEARNING) DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Nur Indriani; Anisa Safitri; Aris Munandar; Yulisan; Radiatul Adwiah; Syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To develop students who can understand social phenomena and actively participate in community life, social science education requires the use of learning models such as PBL. However, many teachers or educators do not fully understand the objectives and even the impact of implementing the PBL model. Therefore, the aim of this research is to examine the extent to which the application of the PBL model in elementary school social studies can enhance students' knowledge, critical thinking, collaboration, motivation, and problem-solving abilities in social studies learning. This research is a qualitative study that uses data collection methods. The procedure in the data collection research involves document analysis, namely: searching for documents related to the impact of the PBL model in elementary school social studies learning, identifying relevant documents, evaluating documents, collecting and organizing documents, investigating documents, and producing results. The PBL (Problem Based Learning) model has a very significant impact on improving the quality of education, especially in the subject of Social Sciences (IPS) in elementary schools. The PBL model influences the improvement of student learning outcomes and motivation. Additionally, using the PBL model for students can develop 21st-century skills, namely enhancing critical thinking skills, increasing student collaboration, and improving problem-solving abilities. Thus, learning Social Sciences (IPS) is not just a subject, but also trains skills that are very much needed by students in their daily lives.